IMPLEMENTASI PROGRAM BINA SANTRI LAPAS (BSL) DOMPET DHUAFA DALAM MENINGKATKAN PEMBINAAN KEPRIBADIAN NARAPIDANA DI LAPAS KELAS IIA CIKARANG - Galih Syafatullah; Markus Marselinus Soge (Yustitia, 2025)
Each correctional institution has its own way of implementing personality development program development. The personality development program is one of the ways to implement the goal of prisoner reintegration. Cikarang Class IIA Correctional Institution provides Personality Development through the Lapas Santri Development Program. (BSL). The purpose of this research is to understand the implementation of the Dompet Dhuafa Prison Santri Development Program in improving the personality development of inmates at Class IIA Cikarang Prison along with its obstacles. In this study, a qualitative research method with a descriptive approach was used. The data collection techniques used by the researcher are observation, interviews, and document studies. The result of this research is the Santri Development Program (BSL) at Class IIA Cikarang Correctional Facility in collaboration with the Dompet Dhuafa Foundation. The implementation of the program mechanisms agreed upon by the Dompet Dhuafa Foundation and Class IIA Cikarang Correctional Facility includes studying fiqh, reading Iqro, Jus Amma, and the Qur'an, religious lectures, and Dai cadre education. Additionally, it aims to improve the inmates' understanding of reading the Qur'an. Obstacles in implementing education include the lack of quantity of teachers from Dompet Dhuafa, the lack of awareness among inmates in participating in the santri coaching program, and the lack of facilities and infrastructure to support the learning process.